2015
DOI: 10.1159/000430498
|View full text |Cite
|
Sign up to set email alerts
|

Group A <b><i>Streptococcus</i></b> Modulates Host Inflammation by Manipulating Polymorphonuclear Leukocyte Cell Death Responses

Abstract: Polymorphonuclear leukocyte (PMN) cell death strongly influences the resolution of inflammatory episodes, and may exacerbate adverse pathologies in response to infection. We investigated PMN cell death mechanisms following infection by virulent group A Streptococcus (GAS). Human PMNs were infected in vitro with a clinical, virulent GAS isolate and an avirulent derivative strain, and compared for phagocytosis, the production of reactive oxygen species (ROS), mitochondrial membrane depolarization and apoptotic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 38 publications
(43 reference statements)
9
17
0
Order By: Relevance
“…GAS can induce death of human neutrophils ( Kobayashi et al., 2003 ; Tsatsaronis et al., 2015 ), however the mechanism remains poorly described. Phosphatidylserine (PS) exposure is a hallmark of the induction of multiple death pathways including apoptosis and pyroptosis ( Wang et al., 2013 ; Man and Kanneganti, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…GAS can induce death of human neutrophils ( Kobayashi et al., 2003 ; Tsatsaronis et al., 2015 ), however the mechanism remains poorly described. Phosphatidylserine (PS) exposure is a hallmark of the induction of multiple death pathways including apoptosis and pyroptosis ( Wang et al., 2013 ; Man and Kanneganti, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…This neutrophil response likely initiates an antimicrobial response, through phagocytosis and bacterial killing, as well as through the deposition of antimicrobial molecules at the site of infection. Furthermore, it is likely that neutrophil presence results in the stimulation of pro-inflammatory signaling cascades which initiates further inflammation pathways leading to perturbed maternal-fetal tolerance and tissue destruction (Marzano et al, 2010 ; Simard et al, 2011 ; PrabhuDas et al, 2015 ; Tsatsaronis et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…35 Recently, it has also been shown that virulent GAS strains are able to modulate the PMN inflammatory response by reducing their apoptotic potential leading to a necrotic form of cell death. 36 However, although the production of high levels of ROS is responsible of the death of keratinocytes, we show that this ROS production also contributes to eliminating the pathogen. This was demonstrated by the growth rates of GAS strains co-cultured with keratinocytes.…”
Section: Discussionmentioning
confidence: 62%